A health risk assessment of heavy metals in people consuming Sohan in Qom, Iran. (2nd October 2018) - Mohammadi, Mohammad Javad; Yari, Ahmad Reza; Saghazadeh, Mojgan; Sobhanardakani, Soheil; Geravandi, Sahar; Afkar, Abolhasan; Salehi, Seyedeh Zahra; Valipour, Aliasghr; Biglari, Hamed; Hosseini, Seyed Ahmad; Rastegarimehr, Babak; Vosoughi, Mehdi; et al.
Abstract: Based on research findings around the globe, the content of heavy metals (HM) has been kept limited in traditional popular pastries. This study was carried out to conduct a health risk assessment of heavy metals (As, Cd, Cu, Ni, Pb, Sn, and Zn) in Qom's Sohan (a kind of traditional Persian saffron brittle toffee) in 2015. Samples were selected randomly from the most popular brands of Sohan workshops in Qom. After the dry digestion of all Sohan samples, 100 different brands were analyzed via inductively coupled plasma atomic emission spectroscopy (ICP-AES). In this study, about 100 brands of Sohan made by vegetable oil or buttery were analyzed. The results showed that the metals level (µg/kg) in specimens for As, Cd, Cu, Ni, Pb, Sn, and Zn ranged 100–300, 10–50, 500–36, 000, 60–550, 30–1750, 45–1700, and 2500–15000, respectively. In addition, health risk assessment showed that consuming the sample Sohan of the study poses no potential risks for children and adults. Results also revealed that although honey consumption has no adverse effect on the local population, concerning the increased pollutants' entry, especially heavy metals, to the natural environment, it is very important to assess the foodstuffs before releasing them into the consumer market. According to the results of the study, an increase in the exposure level of heavy metal could potentially cause different health problems.